A host receptor enables type 1 pilus-mediated pathogenesis of Escherichia coli pyelonephritis. - Lisa K McLellan; Michael R McAllaster; Arthur S Kim; Ľubomíra Tóthová; Patrick D Olson; Jerome S Pinkner; Allyssa L Daugherty; Teri N Hreha; James W Janetka; Daved H Fremont; Scott J Hultgren; Herbert W Virgin; et al. (PLoS Pathogens)
Type 1 pili have long been considered the major virulence factor enabling colonization of the urinary bladder by uropathogenic Escherichia coli (UPEC). The molecular pathogenesis of pyelonephritis is less well characterized, due to previous limitations in preclinical modeling of kidney infection. Here, we demonstrate in a recently developed mouse model that beyond bladder infection, type 1 pili also are critical for establishment of ascending pyelonephritis. Bacterial mutants lacking the type 1 pilus adhesin (FimH) were unable to establish kidney infection in male C3H/HeN mice. We developed an in vitro model of FimH-dependent UPEC binding to renal collecting duct cells, and performed a CRISPR screen in these cells, identifying desmoglein-2 as a primary renal epithelial receptor for FimH. The mannosylated extracellular domain of human DSG2 bound directly to the lectin domain of FimH in vitro, and introduction of a mutation in the FimH mannose-binding pocket abolished binding to DSG2. In infected C3H/HeN mice, type 1-piliated UPEC and Dsg2 were co-localized within collecting ducts, and administration of mannoside FIM1033, a potent small-molecule inhibitor of FimH, significantly attenuated bacterial loads in pyelonephritis. Our results broaden the biological importance of FimH, specify the first renal FimH receptor, and indicate that FimH-targeted therapeutics will also have application in pyelonephritis.